(untitled) (Annals of Bangladesh Agriculture, 2022)
Soybean (Glycine max L.) is mostly grown in the coastal region of Bangladesh, where salinity is a threat for potential harvest. So far there is no salt tolerant variety. In order to extricate high salt tolerant soybean genotypes, 13 selected advanced soybean lines, namely BD 2342, AGS 313, G 00207, Galarsum, G 00209, G 00343, G 00028, G 00221, G 00283, AGS 95, G 00062, G 00041 and BD 2330 along with two varieties viz. BU Soybean 2 and Shohag were grown in pots under polyvinyl house at BSMRAU, Gazipur during February to June 2021 following completely randomized design (CRD) with three replications. The plants were exposed to seawater of electrical conductivity (EC) of 5 dSm-1 and 10 dSm-1 from 2nd trifoliate stage till harvest, where control pots were irrigated with tap water (0.3 dSm-1). Results indicated that there was no significant variation in days to first flowering but significant variation was observed in maturity duration among the genotypes. In saline conditions BD 2330, G 00028 and AGS 313 survived longer days which were 96.36%, 80.29%, and 79.53% days to control at 10 dSm-1, respectively compared to other genotypes. Plants of other genotypes died earlier before reaching maturity, especially at 10 dSm-1. The genotype AGS313 expressed maximum leaf relative water content (RWC) at 5 dSm-1 salinity (97.51% of control), while BD2330 showed the highest RWC at 10 dSm-1 salinity (94.76%). The SPAD value showed stable or an increasing trends in BD 2330, AGS 313 and G 00028, where it was in decreasing trend in other genotypes under saline conditions. Unexpectedly, the leaf K-Na ratio did not show any significant relationship with the salt-tolerance among the genotypes. In case of number of filled pods/plant BD2330 produced the maximum (23.33) at 5 dSm-1 salinity, while the genotype AGS313 showed the highest (16.0) at 10 dSm-1 salinity. Genotypes other than BD2330, AGS313 and G00028 did not perform well in pod set, 100-seed weight and grain yield/plant under saline conditions, even at 5 dSm-1. However, even at the highest salinity (10 dSm-1) the genotypes G00028, BD2330 and AGS313 produced 2.0, 1.9 and 1.83 g/plant seeds, respectively. Whereas, most of the genotypes did not produce any seed at 10 dSm-1. It may be concluded that the genotypes BD2330, AGS313 and G00028 were relatively salt tolerant than other tested genotypes, and can be used as potential genetic resources for further field trials. Ann. Bangladesh Agric. (2022) 26 (1) : 29-48